Decolonial Praxis in Higher Education - Wang, Ru-Jer; Chiang, Wen-Wei; Shih, Yi-Huang; Ku, Min-Sheng; Lin, Jason Cong; Wati, Unik Ambar; Takamiya, Masaki (Journal of Management World, 2025)
Several significant global social movements, including Rhodes Must Fall in the UK, Fees Must Fall in South Africa, Black Lives Matter in the US, and Why is My Curriculum White? in the UK, challenged the traditions and assumptions of modernization, colonialism, and imperialism within the existing education system. Therefore, the issue of decolonization in higher education deserves much attention. By means of literature analysis, this article explored how higher educational institutions can rethink their practices to be more inclusive and equitable by challenging dominant narratives and promoting decolonial methodologies in teaching, curriculum and research. Finally, three reflections are presented: (1) In some regions, decolonization refers to the formal end of colonial rule, while in others, it involves ongoing struggles to dismantle the legacies of colonialism, including economic dependency, cultural erasure, and social inequality; (2) How higher education institutions are engaging with decolonization; (3) Lack of support for marginalized scholars. The authors hope that through the discussion in this article, we can gain a deeper understanding of decolonial praxis in higher education.